1995
DOI: 10.1002/cne.903570308
|View full text |Cite
|
Sign up to set email alerts
|

Development of the olfactory and accessory lobes in the american lobster: An allometric analysis and its implications for the deutocerebral structure of decapods

Abstract: The allometric changes characterizing the growth of the deutocerebrum (midbrain) of the American lobster (Homarus americanus) are studied using computerized three-dimensional reconstructions of serial brain sections. During the embryogenesis of the midbrain, the paired accessory lobes (higher order processing areas) appear later than the paired olfactory lobes (primary olfactory centers), but the former grow faster from their emergence until metamorphosis. The accessory lobes, as they enlarge, shift progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 37 publications
(40 reference statements)
1
49
0
Order By: Relevance
“…In decapods, the axons of olfactory receptor neurons interact with fibers from interneurons and projection neurons in unusual cone-shaped glomeruli located in the olfactory lobe, as has been demonstrated in the Australian yabby (Cherax destructor), red swamp crayfish (Procambarus clarkii), American lobster (Homarus americanus), and Caribbean spiny lobster (P. argus) [Sandeman and Luff, 1973;Mellon and Munger, 1990;Schmidt et al, 1992a;Helluy et al, 1995]. In lobsters, the glomeruli of the olfactory lobe comprise three distinct horizontal zones or compartments that are innervated by different interneurons [Schmidt et al, 1992b;Langworthy et al, 1997;Schmidt and Ache, 1997].…”
Section: Glomerular Neuropilsmentioning
confidence: 81%
“…In decapods, the axons of olfactory receptor neurons interact with fibers from interneurons and projection neurons in unusual cone-shaped glomeruli located in the olfactory lobe, as has been demonstrated in the Australian yabby (Cherax destructor), red swamp crayfish (Procambarus clarkii), American lobster (Homarus americanus), and Caribbean spiny lobster (P. argus) [Sandeman and Luff, 1973;Mellon and Munger, 1990;Schmidt et al, 1992a;Helluy et al, 1995]. In lobsters, the glomeruli of the olfactory lobe comprise three distinct horizontal zones or compartments that are innervated by different interneurons [Schmidt et al, 1992b;Langworthy et al, 1997;Schmidt and Ache, 1997].…”
Section: Glomerular Neuropilsmentioning
confidence: 81%
“…On passing through the OGTN, the OGT projects bilaterally to the eyestalks where it innervates the lateral protocerebrum ( Fig. 1) (Helluy et al, 1995).…”
Section: Olfactory Projection Neuron Morphologymentioning
confidence: 99%
“…Studies in lobsters and crayfish have revealed similar results (Beltz et al, 1990(Beltz et al, , 1992Helluy et al, 1993). Furthermore, it has been supposed that the ingrowing central projections of new sense organs that are continually added throughout development increase the complexity of the developing crustacean brain (Laverack, 1988a(Laverack, , 1988bMellon and Alones, 1993;Helluy et al, 1995).…”
Section: Introductionmentioning
confidence: 89%
“…These authors observed a more than 600-fold increase in brain volume from hatching to 3 kg adult animals and raise the question about the mechanisms that might contribute to this growth in bulk of the brain. The continual integration of in-growing new sensory axons may be part of the answer (Laverack, 1988a(Laverack, , 1988bMellon and Alones, 1993;Helluy et al, 1995). Furthermore, the gradual maturation and refinement of the fiber system of central interneurons has been shown to contribute to this process (Helluy et al, 1993, Harzsch and Dawirs, 1995, 1996 .…”
Section: Postembryonic Proliferation Of Neuronsmentioning
confidence: 99%